Metatarsal Sesamoids: Borges-Napoleon Sign - Morais, Yuri Borges; Felix, Levy da Costa; Azevedo, Jones Aguiar de (Brazilian Journal of Case Reports, 2024)
The metatarsal sesamoids have been well studied due to their consistent presence in humans and relatively common involvement in foot pathologies. The manifestations of sesamoid lesions on imaging depend on the nature of the pathology and generally overlap. During observation in sectional examinations, an anatomical pattern sign of the sesamoid bones of the first metatarsal was identified to be assessed by specialists in diagnostic imaging to note alterations that deviate from this anatomical pattern sign. Would the anatomical pattern sign in question help in the diagnosis of pathological alterations once it has been de-characterized? The presentation of the Borges-Napoleon sign characterizes the normality of the bones involved in the image, making it safe to diagnose pathological alterations that compromise their structure. Therefore, presenting this idealization could help improve medical reports. The sign is described as the "Borges-Napoleon Sign" because of its resemblance to the silhouette of the Frenchman Napoleon Bonaparte and in reference to the creator of the imaging description, Yuri Borges Morais. Pathological alterations such as traumatic injuries, sesamoiditis, dislocations, fractures, and hallux valgus ("bunions"), among others, de-characterize the Borges-Napoleon sign; the absence of the sign is indicative of an abnormality in the metatarsal-sesamoid-phalangeal region.